2021
DOI: 10.13057/biodiv/d220610
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals accumulation in Nerium oleander leaves across urban areas in Setif region, Algeria

Abstract: Abstract. Koucim MA, Belguidoum A, Lograda T, Ramdani M. 2021. Heavy metals accumulation in Nerium oleander leaves across urban areas in Setif region, Algeria. Biodiversitas 22: 3083-3091. Pollution by Metallic trace elements (MTE) has become one of the most serious environmental problems resulting from human activity. Plants, which are the base of the food chain, can take up MTE from the soil solution; hyper-accumulators can store high levels of heavy metals in their aerial parts at high concentrations. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The stations in these municipalities were affected by commercial areas, industrial facilities, quarries, mining, as well as roads with intense road traffic density, causing the epiphytic vegetation to regress (Kar et al 2014;Khastini et al 2019;Kitoko et al 2020;Mcmullin et al 2017;Sett and Kundu 2016). Studies in the Setif region on the bioaccumulation of metallic trace elements showed a close relationship between high levels of heavy metal pollution and the volume of road traffic (Belguidoum et al 2020;Koucim et al 2021).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The stations in these municipalities were affected by commercial areas, industrial facilities, quarries, mining, as well as roads with intense road traffic density, causing the epiphytic vegetation to regress (Kar et al 2014;Khastini et al 2019;Kitoko et al 2020;Mcmullin et al 2017;Sett and Kundu 2016). Studies in the Setif region on the bioaccumulation of metallic trace elements showed a close relationship between high levels of heavy metal pollution and the volume of road traffic (Belguidoum et al 2020;Koucim et al 2021).…”
Section: Discussionmentioning
confidence: 98%
“…There are several methods to monitor air quality, including multivariate physico-chemical analysis, based on air pollution monitoring system and air quality control by network facilities, and biological techniques (Conti and Cecchetti 2001;Khedo et al 2010;Shaban et al 2016). Relatively few studies have relied on the concurrent use of biomonitoring (Belguidoum et al 2021;Kaur and Nagpal 2017). Living organisms used in air quality monitoring offer an important tool for estimating the impact of air pollution, providing data for environmental management (Pirintsos and Loppi 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is useful since the cost is low and it can be used efficiently on a large scale, offering a tool to monitor heavy metal contamination (Antonucci et al 2016;Belguidoum et al 2020. Several higher plants have been used to assess metal contamination in urban and industrial area because of their accumulation properties (Vannucchi et al 2020;Koucim et al 2021, Giniatullin et al 2016. This paper investigates the possibility to use apple trees to monitor and ameliorate the metal(loid) pollution of Chelyabinsk urban areas.…”
Section: Introductionmentioning
confidence: 99%